Designing Deep Scaffolding Based on Realistic Mathematics Education to Address Errors of Slow Learners in Solving Numeracy Problems - Kadek Adi Wibawa; I Gde Dhika Widarnandana; I Made Dharma Atmaja (Proceeding International Conference on Mathematics and Learning Research, 2025)
This study aims to develop an adaptive and contextual numeracy learning model based on deep scaffolding for slow learner (SL) students in inclusive education settings. The model is designed to address common mathematical thinking difficulties experienced by SL students, such as conceptual, procedural, and representational errors. The research method employs a conceptual review approach consisting of four systematic stages: literature mapping, thematic analysis, conceptual synthesis, and theoretical validation by experts in mathematics and inclusive education. The findings indicate that reflective, meaningful, and joyful learning interventions can enhance students’ metacognitive awareness, motivation, and numeracy comprehension. The proposed deep scaffolding model comprises three core components: mindful scaffolding to foster error awareness, meaningful scaffolding to connect prior knowledge with real-life contexts, and joyful scaffolding to create a positive and engaging learning atmosphere. Expert validation yielded an average score of 3.875, indicating that the model is feasible for implementation in inclusive numeracy instruction. The study recommends teacher training in applying contextual and differentiated scaffolding strategies, as well as the development of instructional tools grounded in Realistic Mathematics Education that are responsive to the needs of SL students. This model is expected to make a practical contribution to improving the quality of equitable and empowering numeracy education for all learners.